Macroeconomic Determinants of the Mortgage Loan. / Factores macroeconómicos determinantes del préstamo hipotecario. - KADOCHNIKOVA, E.; BULATOVA, E.; SAFIULLINA, A.; SUYCHEVA, D. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research aims to assess the relationship of macroeconomic indicators and those related to the banking sector of the economy. They will be considered with the volume of mortgage loans granted on the example of the russian economy. It is shown that the increase in the weighted average mortgage rate is correlated with the increase in the volume of mortgage loans; the increase in the average nominal wage contributes to the increase in the volume of mortgage loans. The direct relationship between the volume of mortgage loans and problem mortgage debt can predict the inflating of the "credit" bubble.RESUMEN Esta investigación tiene como objetivo evaluar la relación de los indicadores macroeconómicos y los relacionados con el sector bancario de la economía. Serán considerados con el volumen de préstamos hipotecarios concedidos en el ejemplo de la economía rusa. Se muestra que el aumento de la tasa hipotecaria promedio ponderada, se correlaciona con el aumento del volumen de préstamos hipotecarios; el aumento del salario nominal medio contribuye al aumento del volumen de préstamos hipotecarios. La relación directa entre el volumen de préstamos hipotecarios y la deuda hipotecaria problemática puede predecir la inflación de la burbuja del "crédito".